Rhetorical Devices Used To Make Emphasis In Brian Tracy’s Talk “How To Build A Business That Works” - Christopher Faith; Aylanda Hidayati Dwi Nugroho (Kata Kita: Journal of Language, Literature, and Teaching, 2024)
This research investigates the types of rhetorical devices that Brian Tracy used in his business presentation, three types of rhetorical devices that are mostly used, and how these rhetorical devices are used to make emphasis on his business tips and suggestions. This research used Harris (2018) and Fahnestock (2011) theories on rhetorical devices. The findings showed that Brian Tracy utilized different types of rhetorical devices to aid him in emphasizing his main idea, such as metaphor, simile, sentential adverb, asyndeton, polysyndeton, hyperbole, paralepsis, litotes, and climax. The three most used types of rhetorical devices in his presentation are Metaphor, Sentential Adverb and Simile. Brian Tracy utilized metaphor to create a clearer imagery, sentential adverb to separate the anecdotes and conclusion, and simile to give comparison of two subjects. From the findings, the writer concludes that rhetorical devices can help the presenter in delivering his main points. Rhetorical devices help in emphasizing the main idea and creates a more engaging presentation with the audience, hence creating a more impactful and beneficial presentation.